Design of Student Worksheets Based on Augmented Reality - Kharisma, Ade Diana; Syafii, Wan; Zulfarina, Zulfarina (Journal of Educational Sciences, 2020)
Design innovations on student worksheets need to be developed so that students are motivated to following the learning process. Many students difficult to understand an abstract concept of biology because they can not see directly. We can using Augmented Reality technology in the design of Student Worksheets as one of that innovation. Therefore a descriptive study was conducted to design a Student Worksheet based on Augmented Reality. The design process was carried out in two stages, namely analysis and design. The analysis phase was done by observing using questionnaires and the design stage was done by utilizing various computer software. The result of research is the design of Student Worksheets that is integrated with Augmented Reality, so the student can see the abstract object of biology by 3D AR directly with that technology. This result were expected to be developed and carried out further testing.